Exploring Ocean Biogeochemistry Using a Lab-on-Chip Phosphate Analyser on an Underwater Glider - Birchill, Antony J.; Beaton, A. D.; Hull, Tom; Kaiser, Jan; Mowlem, Matt; Pascal, R.; Schaap, A.; Voynova, Yoana G.; Williams, C.; Palmer, M. (Frontiers in Marine Science, 2021)
The ability to make measurements of phosphate (PO43-) concentrations at temporal and spatial scales beyond those offered by shipboard observations offers new opportunities for investigations of the marine phosphorus cycle. We here report the first in situ PO43- dataset from an underwater glider (Kongsberg Seaglider) equipped with a PO43- Lab-on-Chip (LoC) analyser. Over 44 days, a 120 km transect was conducted in the northern North Sea during late summer (August and September). Surface depletion of PO43- (<0.2 µM) was observed above a seasonal thermocline, with elevated, but variable concentrations within the bottom mixed layer (0.30-0.65 µM). Part of the variability in the bottom layer is attributed to the regional circulation and across shelf exchange, with the highest PO43- concentrations being associated with elevated salinities in northernmost regions, consistent with nutrient rich North Atlantic water intruding onto the shelf. Our study represents a significant step forward in AUV sensor capabilities and presents new capability to extend research into the marine phosphorous cycle and, when combined with other recent Lab-on-Chip developments, nutrient stoichiometry.